2020
DOI: 10.1038/s41420-020-0263-6
|View full text |Cite
|
Sign up to set email alerts
|

Temporal transcriptome analysis of neuronal commitment reveals the preeminent role of the divergent lncRNA biotype and a critical candidate gene during differentiation

Abstract: lncRNA genes can be genic or "intergenic". "Genic" RNAs can be further divided into six biotypes. Through genomewide analysis of a publicly available data set on corticogenesis, we found that the divergent lncRNA (XH) biotype, comprising the lncRNA and the coding gene being in opposite directions in a head-to-head manner, was most prominent during neural commitment. Within this biotype, a coding gene/divergent RNA pair of the BASP1 gene and the uncharacterized RNA loc285696 (hitherto referred as BASP1-AS1) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…At present, only BASP1‐AS1 regulates BASP1 in hNPCs and plays a crucial role in neuronal differentiation. 19 The importance of BASP1‐AS1 in the progression and prognosis of melanoma is still unclear. In this study, we used the subcellular stratification technique to find that BASP1‐AS1 was localized in the nucleus, suggesting that BASP1‐AS1 may be involved in the transcription process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At present, only BASP1‐AS1 regulates BASP1 in hNPCs and plays a crucial role in neuronal differentiation. 19 The importance of BASP1‐AS1 in the progression and prognosis of melanoma is still unclear. In this study, we used the subcellular stratification technique to find that BASP1‐AS1 was localized in the nucleus, suggesting that BASP1‐AS1 may be involved in the transcription process.…”
Section: Discussionmentioning
confidence: 99%
“…Survival analysis showed that functional LncRNAs‐CNV might be a candidate prognostic biomarker for clinical application, and BASP1 ‐AS1 is a new LncRNA that has not been screened out in melanoma, even if it has been found that BASP1‐AS1 regulates BASP1 in HNPCs and plays a key role in neuronal differentiation. 19 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the exact physiological role of BASP1-AS1 in the brain is not fully understood, it could regulate the expression of BASP1. Indeed, a recent study, Prajapati et al highlighted, in "in vitro" model, that BASP1-AS1 regulates BASP1 in human neural progenitor cells, and has a critical role in neuronal differentiation [57]. It seemed that over-expression of BASP1 in adult neurons promotes sprouting [58] and, more specifically, modulate neurite outgrowth in hippocampal neurons [59].…”
Section: Discussionmentioning
confidence: 99%